Documents from Glenn Johnson and F. Taylor Ostrander - Johnson, Marianne F.; Samuels, Warren J., 1933- (Research in the history of economic thought and methodology, 2009)
Volume 27C of Research in the History of Economic Thought and Methodology consists of documents from Glenn Johnson and F. Taylor Ostrander. Part I includes: notes from lectures by James E. Meade on the linking of monetary theory with the pure theory of value (Oxford University, 1932-1933); notes from the Socialist Club at the Cafe Verique in Geneva (Summer 1931); correspondence between Frank H. Knight and F. Taylor Ostrander; index to the Treasury Department papers of F. Taylor Ostrander; and notes on the long and wide-ranging career of F. Taylor Ostrander. Part II presents Glenn Johnson's notes from courses at the University of Chicago (1946); notes from Lloyd Mints' course on money and banking, economics 330 (Fall 1946); incomplete course notes from Milton Friedman's price theory, economics 300B, University of Chicago (Spring 1947); and notes from seminars by John R. Hicks and Tjalling Koopmans, University of Chicago (October 1946).